Matrix Gla protein is associated with coronary artery calcification as assessed by electron-beam computed tomography - Jono, Shuichi; Ikari, Yuji; Vermeer, Cees; Dissel, Paul; Hasegawa, Kotaro; Shioi, Atsushi; Taniwaki, Hiromichi; Kizu, Akane; Nishizawa, Yoshiki; Saito, Shigeru (Thrombosis and haemostasis, 2004)
Matrix Gla protein (MGP) is an extracellular matrix protein with wide tissue distribution. It has been demonstrated that the expression of MGP is detected not only in the normal blood vessels but also calcified atherosclerotic plaques, and that MGP deficient mice develop extensive arterial calcification. MGP is thought to be a regulator of vascular calcification. A recent clinical study demonstrates the association between polymorphisms of the MGP gene and increased risk of myocardial infarction. However, there are no reports of the relationship between serum MGP levels and coronary artery calcification (CAC). We evaluated the severity of CAC using electron-beam computed tomography (EBCT), and measured serum MGP levels by enzyme-linked immunosorbent assay in 115 subjects with suspected coronary artery disease. CAC scores were correlated with traditional risk factors, such as age, gender, hyper-tension, diabetes, hyperlipidemia and smoking. The serum MGP levels were lower in patients with CAC than in those without CAC (p<0.001). As the severity of CAC increased, there was a significant decrease in serum MGP levels. Serum MGP levels (U/L) were 116.7 +/- 20.3, 104.9 +/- 19.2, 95.2 +/- 15.2 and 82.2 +/- 19.7, (medians 115.5, 105.0, 94.8, and 81.9) for the subjects with normal (CAC score=0), mild (CAC score=1 to 99), moderate (CAC score=100 to 400), and severe (CAC score >400) coronary calcification, respectively. We found that serum MGP levels are inversely correlated with the severity of CAC. These data suggest a possible role for MGP in the development of vascular calcification.